KEMISKINAN STRUKTURAL DAN HUBUNGAN PATRON KLIEN NELAYAN DI DESA MAITARA KECAMATAN TIDORE UTARA KOTA TIDORE KEPULAUAN - Suleman, Akbar; Pratiknjo, Maria Heny; Sandiah, Nasrun (Universitas Sam Ratulangi, 2019)
In the social context, the characteristics of the fishing communities vary with the characteristics of the farming community, along with the difference in the characteristics of the resources at hand. Fishermen face access resources that are currently still are open access. Characteristics of resources such as these cause the fishermen must be moving in order to obtain maximum results, so the risk becomes very high. The condition of the resources that are at risk of the fishermen have a hard character, firm, and open.The fishing Maitara can be grouped into several groups of fishermen i.e. that traditional fishing activities of catching fish by using a capture tool that still are simple so bring a limited range that is the marine environment Maitara.With the economic limitations due to uncertainty resulting from the income of fishermen were forced to seek refuge to another person that is the owner of the ship in order to guarantee the sustainability of life. The pattern of the working relationship which is reflected in the relationship between the client-patron and owner laborer fishermen is to guarantee a growing socio-economic communities. The mechanism of this working relationship are dependency, patron (owner fishers) had the capital and capture tool while clients (workers) have the power to run the business of the owner of the boat.Patron-client relationships can drive economic activity because it provides employment for workers of the fishing result in accordance agreement between them so influential in meeting the needs of their life. Keywords: fishermen, patron-client, resources